Bismuth with abundant defects for electrocatalytic CO2 reduction and Zn–CO2 batteries. Issue 22 (24th February 2022) - Wang, Yuchao; Huang, Zisheng; Lei, Yongpeng; Wu, Jiao; Bai, Yu; Zhao, Xin; Liu, Mengjie; Zhan, Longsheng; Tang, Shuaihao; Zhang, Xiaobin; Luo, Fenghua; Xiong, Xiang
Abstract : The abundant defects in bismuth boosted the formate selectivity of electrocatalytic CO2 reduction. Abstract : To regulate the electronic structure of Bi sites and enhance their intrinsic activity, metal Bi with abundant defects was constructed. The optimized sample displayed a higher selectivity (93.9% at −0.9 V) and a larger current density (−10 mA cm −2 at −1.0 V) towards electrocatalytic CO2 reduction to formate, which can be mainly attributed to abundant defect sites and the optimized electronic structure. The assembled Zn–CO2 batteries displayed a power density of 1.16 mW cm −2 and a cycling stability up to 22 h. This work deepens the research of Bi-based catalysts towards CO2 transformation and related energy devices.